Systemic inflammatory response syndrome in acute‐on‐chronic liver failure: Relevance of 'golden window': A prospective study. Issue 12 (10th November 2017) - Choudhury, Ashok; Kumar, Manoj; Sharma, Barjesh C; Maiwall, Rakhi; Pamecha, Viniyendra; Moreau, Richard; Chawla, Yogesh K; Duseja, Ajay; Mahtab, Mamun; Rahman, Salimur; Hamid, Saeed S; Butt, Amna S; et al.
Abstract: Background and Aim: Systemic inflammatory response syndrome (SIRS) is an early marker of sepsis and ongoing inflammation and has been reported in large proportion of acute‐on‐chronic liver failure (ACLF) patients. Whether sepsis is the cause or the result of liver failure is unclear and is vital to know. To address this, the study investigated the course and outcome of ACLF patients without SIRS/sepsis. Methods: Consecutive ACLF patients were monitored for the development of SIRS/sepsis and associated complications and followed till 90 days, liver transplant or death. Results: Of 561 patients, 201 (35.8%) had no SIRS and 360 (64.2%) had SIRS with or without infection. New onset SIRS and sepsis developed in 74.6% and 8% respectively in a median of 7 (range 4–15) days, at a rate of 11% per day. The cumulative incidence of new SIRS was 29%, 92.8%, and 100% by days 4, 7, and 15. Liver failure, that is, bilirubin > 12 mg/dL (odds ratio [OR] = 2.5 [95% confidence interval CI = 1.05–6.19], P = 0.04) at days 0 and 4, and renal failure at day 4 (OR = 6.74 [95%CI = 1.50–13.29], P = 0.01), independently predicted new onset SIRS. Absence of SIRS in the first week was associated with reduced incidence of organ failure (20% vs 39.4%, P = 0.003), as was the 28‐day (17.6% vs 36%, P = 0.02) and 90‐day (27.5% vs 51%, P = 0.002) mortality. The 90‐day mortality was 61.6% in the total cohort and that for those having no SIRS and SIRS at presentation were 42.8% and 65%, respectively ( P < 0.001). Conclusion: Liver failure predicts the development of SIRS. New onset SIRS in the first week is an important determinant of early sepsis, organ failure, and survival. Prompt interventions in this 'golden window' before development of sepsis may improve the outcome of ACLF.